Lineabilidade em conjuntos de funções reais que atingem o máximo em um único ponto - Nogueira, Tony Kleverson (2014)
In this paper we study the concept of lineability and its recent applications to some sets of continuous real functions. These sets are formed by functions that achieve the absolute maximum in a single point of its domain. In the first chapter we consider the real line and its closed and semi-closed domais as intervals for these functions. In the second chapter we study more general results than those in the previous chapters. In the third chapter we present the theory of degree of continuous applications of Sn in Sn as a tool to demonstrate the Borsuk-Ulam theorem. This result is used a crucial tool in Chapter 2.